Processing Used Cooking Oil into Economically Valuable Products as an Effort to Utilize Household Waste for the Istiqomah Majlis Taklim Women in Korong Olo Bangau Nagari Ketaping Batang Anai District - Kurniawati, Desy; Dewata, Indang; Fadhilah, Fadhilah; Mulia, Melindra; Ningsih, Sherly Kasuma Warda; Veronita, Silvi; Marlini, Rahmida; Fatmawati, Rani (Pelita Eksakta, 2025)
Nagari Ketaping in Batang Anai District has great potential for culinary tourism, especially through traditional fried snack vendors such as sala lauak. However, the extensive use of cooking oil in these activities leads to the generation of used cooking oil (jelantah), which poses serious health and environmental risks. Repeated use of the oil produces free radicals and carcinogenic substances that may cause degenerative diseases, while improper disposal into waterways leads to pollution and ecosystem damage. This community service program aims to educate and raise awareness among members of the majlis taklim in Nagari Ketaping about the dangers of used cooking oil and to demonstrate its potential for conversion into economically valuable products. The main participants are housewives who also operate small fried snack businesses. The outcomes include a scientific publication in Pelita Eksakta Journal (FMIPA UNP), a video documentation, and online media dissemination through Berita Minang.